2007
DOI: 10.1063/1.2748767
|View full text |Cite
|
Sign up to set email alerts
|

Marked differences in volume phase transitions between gel and single molecule in DNA

Abstract: Volume phase transitions of a DNA gel and a single giant DNA chain caused by spermidine 3+ ͑SPD 3+ ͒ were investigated. The change in volume for the single DNA ͑V / V 0 ϳ 10 −5 ͒ was four orders of magnitude greater than that for the DNA gel ͑ϳ10 −1 ͒, while the critical SPD 3+ concentration for the gel ͑1.8 mM͒ was one order of magnitude greater than that of the single DNA ͑0.12-0.25 mM͒ at the same pH 6.86. We tried to describe mean-field theories with virial expansion, which is valid for the coil-globule tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…The transition was produced by adding acetone to the solution: at about 60 vol.% acetone the DNA hydrogel suddenly collapses to a volume about 1/15 of that in the swollen state. Similar, but less marked transition is found upon increasing the concentration of divalent calcium cations [112,113], of spermidine, a trivalent cation [114], and of cationic surfactant [115,116]. This multivalent cation induced collapse is interpreted as a result of the association of DNA double strands that follows their charge neutralization [112].…”
Section: Hydrogelsmentioning
confidence: 74%
“…The transition was produced by adding acetone to the solution: at about 60 vol.% acetone the DNA hydrogel suddenly collapses to a volume about 1/15 of that in the swollen state. Similar, but less marked transition is found upon increasing the concentration of divalent calcium cations [112,113], of spermidine, a trivalent cation [114], and of cationic surfactant [115,116]. This multivalent cation induced collapse is interpreted as a result of the association of DNA double strands that follows their charge neutralization [112].…”
Section: Hydrogelsmentioning
confidence: 74%
“…25 The observed differences may be related to the different contour lengths of 9 while, as mentioned in the first section, it is 166 nm for ss-DNA gels subjected to the swelling tests. Thus, the number of Kuhn segments N equal to 560 and 83 for the single DNA molecule and for the DNA network chain, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…23 Further, Mayama et al observed first-order volume phase transitions in gels and solutions of DNA induced by spermidine, a trivalent cation. 25 Although DNA hydrogels attracted interest in recent years, [26][27][28][29][30] formation conditions of a cross-linked DNA network starting from single DNA strands as well as the hydrogel properties such as viscoelasticity, swelling and thermal behavior have not been investigated in detail. Recently, we investigated the rheological behavior of DNA gels formed by solution cross-linking of ds-DNA at a concentration of 9.3 w/v %.…”
Section: Introductionmentioning
confidence: 99%
“…3. By introducing angular dependence on the binary interaction between the segments, the free energy is reformulated as follows (37,38):…”
Section: Theoreticalmentioning
confidence: 99%
“…1 D. Concerning the physicochemical action of SPD(3þ) on the conformational transition of DNA, we have presented rather detailed theoretical discussions in previous papers (37,38), and therefore skip the theoretical details and present here only a short explanation. In contrast to the case of shrinking by Fis, DNA is tightly compacted by SPD, that is, there is a 30-to 60-fold difference in the DNA segment density between the shrunken and compact states (see, e.g., Fig.…”
Section: Theoreticalmentioning
confidence: 99%